De-novo nonalcoholic steatohepatitis is associated with long-term increased mortality in liver transplant recipients. Issue 7 (July 2018) - Gitto, Stefano; de Maria, Nicola; di Benedetto, Fabrizio; Tarantino, Giuseppe; Serra, Valentina; Maroni, Lorenzo; Cescon, Matteo; Pinna, Antonio D.; Schepis, Filippo; Andreone, Pietro; Villa, Erica
Abstract : Objective: Patients who have undergone transplantation often develop metabolic syndrome (MetS) and de-novo nonalcoholic fatty liver disease (NAFLD). Our aim was to evaluate the impact of metabolic disease on cardiovascular and neoplastic risk and survival. Patients and methods: Data from patients who underwent transplantation between 2000 and 2005 in two Italian transplant centers were analyzed. Cox regression analysis was carried out for predictors of de-novo NAFLD and nonalcoholic steatohepatitis (NASH), cardiovascular events, de-novo extrahepatic cancers, and survival. Survival analysis was completed using the Kaplan–Meier method. A P value less than 0.05 was considered significant for all tests. Results: De-novo NAFLD was found in one-fifth of 194 patients. Patients with de-novo NAFLD fulfilled the criteria of MetS in 74.4% of cases, while patients without de-novo NAFLD in 29.8% ( P =0.000). On multivariate analysis, MetS correlated independently with de-novo NAFLD and this emerged as an independent predictor of cardiovascular events and as a relevant risk factor for solid extrahepatic cancer. Data on smoking habits, which represent a consolidated risk factor for cardiovascular events and cancer in both the general population and patients who have undergone transplantation, are not available. In the subset of histologically proven NASH, it was the strongest predictor of long-term survival (hazard ratio=4.133, 95% confidence interval: 1.385–12.331, P =0.011). Conclusion: Post-transplant NAFLD represented a strong risk factor for cardiovascular atherosclerotic disease and solid extrahepatic cancer, whereas de novo histologically proven NASH was an independent predictor of long-term mortality. Abstract : Supplemental Digital Content is available in the text.